Pre-vocational business education : draft copy - Newfoundland and Labrador. Department of Education. Division of Instruction. (Division of Instruction, Department of Education, 1978)
Pre-vocational Business Education (Draft Copy) Grade nine unit of prevocational business education -- Grade ten unit of prevocational business education -- Grade eleven unit of prevocational business education